DESIGN, DEVELOPMENT, AND CHARACTERIZATION OF CURCUMIN-LOADED NANO TABLET IN ENDOMETRIOSIS TREATMENT - ABHINI, UMMANGALBALAN; MARIAPPAN, GURUSAMY; KUMAR, BHAVNA (International Journal of Applied Pharmaceutics, 2025)
Objective: The goal was to simplify the manufacture of curcumin-loaded-nanosponges (CUNS) and test their vaginal delivery of CU for endometriosis in mice. Methods: The independent parameters of CU-β-Cyclodextrin (CU-β-CD) NS generation were improved using box-behnken design (BBD). BBD with three factors and three levels was used for the studies. The study used carbonyldiimidazole as a cross-linking agent and lyophilization to create CU-β-CDNS. The anti-endometriosis activity of nano-tablet was tested in mice with peritoneal endometriosis. Results: The mean particle size was 76.78–154.56 nm, and the encapsulation effectiveness was 76.62–86.68%. Transmission Electron Microscopy showed that the polymer encapsulated CU. In vitro antioxidant activity showed that CU and CUNS had SC50 values of 5243.52±389.92 and 187.36±16.78 μg/ml, respectively. Bio-adhesion studies showed hydroxypropyl methylcellulose and xanthan gum performed better. The F1 and F2 formulations had better in vitro drug release at 12 h, with values of 97.12±2.38 and 95.34±3.24%, respectively. Photostability and simulated intestinal fluid testing were good. Endometriosis mice had leukocyte infiltration and fibrosis, while control mice had increased stromal vessel density and intact epithelium. However, CU nanogel greatly alleviated these issues. Histopathology demonstrated CUNS-pill corrected endometrial pathology. Conclusion: The study advised CUNS-pill for endometriosis treatment.